2023
DOI: 10.3390/molecules28020645
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Cosmetic Filters Based on Nanomaterials Composed of Titanium Dioxide Nanoparticles

Abstract: The following work describes the synthesis of new physical filters based on TiO2/SiO2 and TiO2/Ag nanostructures. Titanium dioxide nanoparticles (TiO2 NPs) were applied as control material and a popular physical UV filter. The advantage of using materials on the nanometer scale is the elimination of the skin whitening effect that occurs when using photoprotective cosmetics containing titanium dioxide on a macro scale. In addition, the silica coating makes the material less harmful, and the silver coating enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Titanium dioxide (TiO 2 ) is an inorganic UV filter present as both nano (22.0%) and micro (28%) forms in child sunscreens. Titanium oxide is considered a more photochemically stable and less skin irritating filter than most organic filters, but it can generate reactive oxygen species (ROS) when exposed to UV radiation, leading to potential adverse effects [53][54][55]. Therefore, since 2019, titanium dioxide can only be used as a nanomaterial when coated with inert shells like silica, hydrated silica, alumina, aluminium hydroxide, aluminium stearate, stearic acid, trimethoxycaprylylsilane, dimethicone or simethicone, or with some combinations thereof (Annex VI, Regulation No.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is an inorganic UV filter present as both nano (22.0%) and micro (28%) forms in child sunscreens. Titanium oxide is considered a more photochemically stable and less skin irritating filter than most organic filters, but it can generate reactive oxygen species (ROS) when exposed to UV radiation, leading to potential adverse effects [53][54][55]. Therefore, since 2019, titanium dioxide can only be used as a nanomaterial when coated with inert shells like silica, hydrated silica, alumina, aluminium hydroxide, aluminium stearate, stearic acid, trimethoxycaprylylsilane, dimethicone or simethicone, or with some combinations thereof (Annex VI, Regulation No.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of nanotechnology into cosmetic formulations is regarded as the most current and developing technology currently accessible [105]. Cosmetic producers use nanoscale compounds to enhance UV protection [109][110][111][112], facilitate deeper skin penetration [113][114][115][116][117], prolong the effects [118,119], intensify color [120,121], improve finish quality [121], stability [118,122], and provide lower toxicity [87,115]. Kojic acid dipalmitate has been widely utilized in the cosmetics industry.…”
Section: Nanotechnology Formulations Of Kojic Acid Dipalmitatementioning
confidence: 99%
“…Moreover, it is known that metallic NPs coated with silica do not lose their unique properties. [176,177] The properties of the core are influenced, among others, by the thickness and porosity of the shell. Taking into account scientific reports, it was found that a thin and homogenous silica coating on the surface of core-shell nanostructures provides colloidal stability to the nanocomposite without disturbing their properties.…”
Section: Core-shell Nanostructuresmentioning
confidence: 99%
“…Silica used as a coating in nanostructures primarily reduces the potential toxicity of the nanomaterial and makes it more biocompatible, which is important considering its subsequent applications in the medical industry. Moreover, it is known that metallic NPs coated with silica do not lose their unique properties [176,177] . The properties of the core are influenced, among others, by the thickness and porosity of the shell.…”
Section: Medical Application Of Ag/au@silica Core‐shell Nanostructuresmentioning
confidence: 99%